Lipidomic analysis of cerebrospinal fluid by mass spectrometry–based methods. Issue 1 (9th December 2014) - Colsch, Benoit; Seyer, Alexandre; Boudah, Samia; Junot, Christophe
Abstract: Lipids are natural substances found in all living organisms. Essential to the integrity of cell membranes, they also have many biological functions linked to energy storage and cell signaling, and are involved in a large number of heterogeneous diseases such as cancer, diabetes, neurological disorders, and inherited metabolic diseases. Lipids are challenging to analyze because of their huge structural diversity and numerous species. Up to now, lipid analysis has been achieved by targeted approaches focusing on selected families and relying on extraction protocols and chromatographic methods coupled to various detectors including mass spectrometry. Thanks to the technological improvements achieved in the fields of chromatography, high‐resolution mass spectrometry and bioinformatics, it is possible to perform global lipidomic analyses enabling the concomitant detection, identification and relative quantification of many lipid species belonging to different families. The aim of this review is to focus on mass spectrometry–based methods to perform lipid and lipidomic analyses and on their application to the analysis of cerebrospinal fluid.